ADIPOSE TISSUE DISTRIBUTION AND SURVIVAL AMONG WOMEN WITH NON-METASTATIC BREAST CANCER - Bradshaw, Patrick T. (Obesity (Silver Spring), 2019)
OBJECTIVE: Previous studies of breast cancer survival have not considered specific depots of adipose tissue such as subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). METHODS: We assessed these relationships among 3,235 women with stage II/III breast cancer diagnosed between 2005–2013 at Kaiser Permanente Northern California and 2000–2012 at the Dana Farber Cancer Institute. SAT and VAT areas (cm(2)) were calculated from routine CT scans within 6 (median: 1.2) months of diagnosis, covariates were collected from electronic health records, and vital status was assessed by death records. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox regression. RESULTS: SAT and VAT ranged from 19.0–891 cm(2) and 0.484–454 cm(2), respectively. SAT was related to increased risk of death [127 cm(2) increase, HR (95% CI): 1.13 (1.02, 1.26)] but no relationship with VAT [78.18 cm(2) increase: 1.02 (0.91, 1.14)]. An association with VAT was noted among women with stage II cancer [stage II: 1.17 (0.99, 1.39); stage III: 0.90 (0.76, 1.07); p-interaction: <0.01]. Joint increases in SAT and VAT were associated with mortality above either alone [simultaneous 1-SD increase: 1.19 (1.05, 1.34)]. CONCLUSIONS: SAT may be an underappreciated risk factor for breast cancer-related death.